Double-hatting in EU external engagements: EU Special Representatives and the question of coherence post-Lisbon - Mateja Peter (Stiftung Wissenschaft und Politik (SWP), 2012)
Coherence is of continuing significance for the European Union's external activities, particularly when it comes to countries and regions embroiled in or emerging from conflict. Here, the EU's shorter-term concerns about instabilities and security need to be reconciled with plans and commitments for longer-term engagements. The question of coherence is especially relevant when it comes to the European External Action Service (EEAS). The mid-2013 review of the EEAS is intended to evaluate the organisational aspects of this body, but the High Representative and member states should take this opportunity to engage in a more strategic assessment of how the EEAS could contribute to foreign policy coherence. One aspect in need of consideration is the coordination of activities between the European Union Special Representatives (EUSR) and the EEAS. In particular, the viability and challenges of double-hatting in-country EUSRs as Heads of Delegations should be addressed
Keywords: 320